The reform of King Josiah and the composition of the Deuteronomistic history - Eynikel, Erik (Oudtestamentische studiën, 1996)
The Reform of King Josiah and the Composition of the Deuteronomistic History defends the thesis that 1 and 2 Kings arose in three redactional phases. The first author described the history of Judah and Israel from Solomon to Hezekiah (1 Kgs 3-2 Kgs 20). A second redactor, inspired by Deuteronomy, completed the history up to King Josiah and altered the work of his predecessor. The work of these two redactors was limited to Kings. A third redactor, also inspired by Deuteronomy, completed the history up to the exile. Unlike the preceding authors he reworked the whole of the deuteronomistic history. The first part of this study subjects the regnal formulae to a critical analysis. The second part studies 2 Kgs 23:1-30 as a text case in detecting the redactional structure of Kings.